2016
DOI: 10.1007/s10815-016-0839-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of younger age on treatment discontinuation in insured IVF patients

Abstract: Purpose This retrospective cohort study aimed to determine whether age influences treatment discontinuation among insured patients undergoing in vitro fertilization (IVF). We hypothesized that the youngest patients would be the least likely to discontinue treatment. Methods All women age 18-42 who underwent their first fresh, non-donor IVF cycle from 2002 to 2013 were followed until a live birth was achieved, until they discontinued treatment at our center (not presenting for treatment for a one-year period), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…However, if treatment termination were due solely to poor prognosis, then young women would be the least likely to stop treatment, which is not the case. We previously found that although women aged 40–42 years were the most likely to stop treatment, women <30 years old were as likely to stop treatment as those aged 30 to <40 years, indicating that factors other than prognosis affect decision making (19). However, women aged <30 and 40–42 years were the least likely to report stress as the reason why they terminated treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, if treatment termination were due solely to poor prognosis, then young women would be the least likely to stop treatment, which is not the case. We previously found that although women aged 40–42 years were the most likely to stop treatment, women <30 years old were as likely to stop treatment as those aged 30 to <40 years, indicating that factors other than prognosis affect decision making (19). However, women aged <30 and 40–42 years were the least likely to report stress as the reason why they terminated treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have examined factors associated with treatment discontinuation, most only included patients with IVF insurance coverage. (3)(4)(5)(6)(7)(8)(9)(10)(11)(16)(17)(18)(19)(20)(21)(22)(23)(24) Therefore, a significant gap in our understanding of IVF treatment discontinuation persists given that the majority of Americans do not have IVF insurance coverage (25) and have limited access to fertility treatment. (26) The primary aim of this study was to investigate the association between IVF insurance coverage and treatment discontinuation over one year following any first IVF cycle that did not result in a live birth.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, couples who discontinue treatment after a failed cycle may have different exposure characteristics than couples who undergo a subsequent cycle. For example, advanced maternal age and poor prognosis has been associated with an increased rate of treatment discontinuation (Dodge et al, 2017). Alternatively, many couples discontinue treatment because they have conceived spontaneously (Domar et al, 2018).…”
Section: Discussionmentioning
confidence: 99%